PENGARUH LEVERAGE UKURAN PERUSAHAAN PROFITABILITAS TERHADAP FEE AUDIT - Shinta Aditia Putri; Dirvi Surya Abbas; Hesty Ervianni Zulaecha (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2022)
This study aimed to examine: 1) the effect of leverage on profitability 2) effect of firm size 3) effect of profitability 4) effect fee audit. This research study considered causative. The population was proverty and real estate companies listed on the Indonesia Stock Exchange in 2017 until 2021. The research sample was determined by the method of purposive sampling to obtain a sample of 14 companies. Types of data used are secondary data and methods of analysis used is multiple regression. This study concluded that leverage was significantly influence profitability, 2) Firm size is not significantly influence the profitability. In this study suggested that further research should consider expanding the sample beyond the properti and real estate sector and extend the observation period, so that the results obtained can be generalized. And also the number of other factors that need to be considered profitability by further research. Subsequent researchers can conduct research associated with profitability, using a variety of relevant variables, which certainly influenced on the performance and development of the profitability of a company.